2023
DOI: 10.11591/ijphs.v12i1.21921
|View full text |Cite
|
Sign up to set email alerts
|

Peer facilitators’s role to support pregnant women in utilizing HIV services during the COVID-19 pandemic

Abstract: <p>Human immunodeficiency virus (HIV) prevalence on pregnant women in Indonesia is estimated around 0.3%. The prevention of mother-to-child disease transmission (PMTCT) program has been implemented nationally since 2008, though, less than 50% of the total pregnant women each year get an HIV test and only 18% of those who are HIV positive get antiretroviral (ARV) treatment until now. COVID-19 pandemic, occurred since 2019, has brought significant changes to public health aspects including the utilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…One form of support that can be provided is the involvement of women living with HIV as peer supporters to assist HIV-positive pregnant women throughout their pregnancy. Our previous research indicated that HIV-positive pregnant women who did not receive help from peer mentors were 2.96 times more likely to face difficulties in accessing ARV treatment services compared to those who did receive assistance [3].…”
mentioning
confidence: 99%
“…One form of support that can be provided is the involvement of women living with HIV as peer supporters to assist HIV-positive pregnant women throughout their pregnancy. Our previous research indicated that HIV-positive pregnant women who did not receive help from peer mentors were 2.96 times more likely to face difficulties in accessing ARV treatment services compared to those who did receive assistance [3].…”
mentioning
confidence: 99%